Association of concussion with high school academic standing: sex, school grade and race as stratifiers. Issue 5 (12th September 2022) - Takagi-Stewart, Julian; Qiu, Qian; Mills, Brianna; Avery, Aspen D; Muma, Amy; Vavilala, Monica S
Abstract : Introduction: The purpose was to examine the association between concussion history and academic standing among high school students, and whether the association varies by sex, school grade and race/ethnicity. Methods: Data from the 2019 Youth Risk Behaviour Survey were used for our cross-sectional study. Exposure was self-reported history of concussions in the past 12 months. Outcome was self-reported academic standing in the past 12 months. Poisson regression was used to analyse the exposure–outcome association, and whether there were differences by our stratifying variables. Results: Having a history of concussion in the past 12 months was significantly associated with a higher risk of poor academic standing during the same period, and the association varied by race/ethnicity. Discussion: Youth with a history of concussion may be at risk for poorer academic standing, indicating to the importance of prevention. Future studies are needed to examine the interaction of race/ethnicity on the presented association.